Preparation method of lightweight high-strength zirconia-based heat insulation film

By growing zirconia on the surface of graphene oxide nanosheets and using vacuum filtration technology to assemble it, a zirconia-based composite film with a shell-like layered structure was prepared, which solved the complex and time-consuming preparation method of existing zirconia-based thermal insulation materials. problem, realizing the preparation of lightweight, high-strength, low thermal conductivity thermal insulation materials.

CN119330705APending Publication Date: 2025-01-21BEIHANG UNIV

Patent Information

Application Number
CN202411496154.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing preparation methods of zirconia-based thermal insulation materials have problems such as complex process conditions, long time consumption and major influences by environmental factors, making it difficult to effectively prepare composite materials with lightweight, high strength and low thermal conductivity.

Method used

The use of graphene nano tablets is used as a template, which grows oxidized on its surface to form a micro -nano -structure unit similar to the sandwich structure. It is efficiently assembled by vacuum filtering technology to prepare a composite composite film with an imitation shell -like structure structure. Essence

Benefits of technology

The preparation of the oxidized cymbal composite film with light quality, high -strength, and low heat conduction coefficients has been achieved, and it is difficult for the existing heat insulation materials to improve the mechanical performance and thermal insulation performance. At the same time, this method is simple, environmentally friendly, and not easily affected by environmental factors. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330705A_ABST
    Figure CN119330705A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of thermal insulation materials, and relates to design of a micro-nano structure of a material and an assembly strategy of a micro-nano structure unit, in particular to a preparation method of a zirconium oxide-based thermal insulation film with light weight, high strength and low heat conductivity coefficient. The preparation method comprises the following steps: growing zirconium oxide on the surface of a graphene oxide nanosheet serving as a template, and finally, efficiently assembling the graphene oxide nanosheet through vacuum filtration to obtain the zirconium oxide-based composite film with a layered structure. The specific method comprises the following steps: (1) mixing graphene oxide with zirconium salt to prepare a graphene oxide-zirconium oxide nanosheet structure unit; (2) preparing an organic matter binder solution; and (3) mixing the nanosheets in the step (1) with the solution in the step (2), and performing vacuum filtration to obtain a composite film, thereby finally realizing the preparation of the light high-strength zirconium oxide-based heat-insulating film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of thermal insulation materials, relates to the design of material micro-nano structures and the assembly strategy of micro-nano structural units, and specifically relates to a method for preparing a lightweight, high-strength, low-thermal-conductivity zirconium oxide-based thermal insulation film. Background Art

[0002] When thermal insulation materials are used in complex environments, they must meet two basic requirements: first, the material must have extremely low thermal conductivity to effectively prevent heat transfer; second, the material must be able to withstand thermal shock or load shock to maintain a stable internal structure. This dual requirement means that thermal insulation materials should have both low thermal conductivity and excellent mechanical properties.

[0003] In the research and design of thermal insulation materials, the first thing is to choose a suitable low thermal conductivity thermal insulation material. In the past few hundred years, the thermal conductivity of traditional crystalline ceramic materials has been deeply studied. However, there are very few related explorations on the thermal conductivity properties of amorphous materials. Preliminary studies in recent years have shown that the thermal conductivity of amorphous ceramic materials is usually lower than that of the corresponding crystalline materials. Therefore, the preparation of new amorphous ceramic nanostructure units through phase control has become a new direction for the development of thermal insulation ceramic materials. Secondly, constructing a porous structure is an effective means for thermal insulation materials to limit convection and reduce the external radiation of materials. Nature is the best teacher for mankind. There are many thermal insulation materials with micro-nano structures in nature, such as shells, which not only have good thermal insulation properties, but also achieve excellent mechanical properties such as high strength and high toughness.

[0004] Zirconia has the advantages of high temperature resistance, wear resistance, corrosion resistance, and high strength, and is widely used in industrial and agricultural production, aerospace, and energy fields. With the continuous advancement of science and technology, zirconia ceramic materials have occupied an increasingly important position in the field of high-temperature thermal insulation. They can be used for thermal barrier coatings of gas turbine blades and fuel nozzles of rocket engines to reduce the surface temperature of components and extend the life of the engine; they can also be used as thermal insulation tiles for aircraft shells to effectively block the extremely high temperatures generated during high-speed flight and protect the internal structure of the space shuttle from damage. In summary, amorphous zirconia can be used as nanostructure units for assembly, and bionic layered structures can be introduced to prepare high-performance thermal insulation materials.

[0005] At present, a variety of assembly strategies have been developed to prepare biomimetic zirconia-based thermal insulation materials, but there are inevitable problems. For example, the ice template method requires the regulation of multiple parameters, the electrophoretic deposition method has the disadvantages of difficult process condition control and great influence of environmental factors, the layer-by-layer self-assembly method has poor efficiency, and the assembly liquid is easily contaminated. Therefore, it is urgent to develop a simple and effective assembly method to prepare lightweight, high-strength, and low-thermal-conductivity zirconia-based composite materials with a variety of biomimetic structures. Summary of the invention

[0006] The present invention proposes an innovative solution to the limitations of the prior art, such as complex process conditions, time-consuming, and being greatly affected by environmental factors. The method uses readily available graphene oxide nanosheets as templates to grow green and pollution-free zirconium oxide on their surfaces to form micro-nano structural units similar to sandwich structures, which are then efficiently assembled through vacuum filtration technology to obtain a zirconium oxide-based composite film with a shell-like layered structure, and the film has excellent mechanical properties and thermal insulation properties. The method comprises the following steps:

[0007] The first step is to add a buffer solution with a pH of 7-9 to a round-bottom flask filled with 100-400 mL of deionized water, add 10-40 mg of graphene oxide nanosheets after the pH stabilizes, stir evenly to obtain a brown-yellow suspension, then add 0.01-0.30 g of zirconium salt, heat in a water bath to 40-90 ° C and react for 1-3 hours. After the reaction is completed, the product is centrifuged and washed, and the precipitate is evenly dispersed with deionized water to obtain a graphene oxide @ zirconium oxide nanosheet structural unit, and the volume is fixed for subsequent use;

[0008] The second step is to prepare an organic binder solution by adding 1.0-6.0 g of organic matter into a beaker containing 40 mL of deionized water to dissolve it;

[0009] The third step is to add 5-50 mg of graphene oxide @ zirconium oxide nanosheets, 1-5 mL of organic binder solution, and 30 mL of deionized water into a small beaker in sequence, stir at room temperature for 5-20 hours, then use vacuum filtration assembly technology to extract the film, and place the obtained composite film in a 50°C oven for drying.

[0010] In the present invention, unless otherwise specified, the drugs used can be used directly without further purification.

[0011] In the present invention, unless otherwise specified, the devices, instruments, equipment, materials, processes, methods, steps, preparation conditions, etc. used are those conventionally used in the art or can be easily obtained by a person of ordinary skill in the art according to the techniques conventionally used in the art.

[0012] Furthermore, in the first step, the preferred buffer pair is hydrochloric acid and tris(hydroxymethyl)aminomethane; the zirconium salt may be zirconium nitrate, zirconium sulfate, zirconium oxychloride octahydrate, etc.; and the preferred pH value of the buffer solution for adjusting the pH value is 7.6.

[0013] Furthermore, in the first step, deionized water is used for washing 3-5 times during centrifugal washing, and the centrifugal speed is 4000-8000 r / min, preferably 6000 r / min.

[0014] Furthermore, the organic matter in the second step can be selected from polyvinyl alcohol, sodium carboxymethyl cellulose, polyvinyl pyrrolidone and the like.

[0015] Furthermore, the composite film finally obtained has a shell-like layered structure, and the film is light (density is 20-60 mg / cm 3 ), high strength (tensile strength is 60-200MPa), high toughness (toughness is 0.10-3.00MJ / m 3 ), outstanding thermal insulation performance (thermal conductivity is 30-70mW / (m·K)) and other advantages.

[0016] Compared with the existing method for preparing zirconium oxide-based thermal insulation films, the present invention has the following advantages:

[0017] 1. The raw materials used in the present invention are green, environmentally friendly, affordable, and easily available, and the preparation method is simple, time-saving, not easily affected by environmental factors, and can be achieved without the need for large and expensive instruments.

[0018] 2. The composite film prepared by the present invention has the characteristics of light weight, high strength and toughness, excellent thermal insulation performance, etc., which overcomes the difficulty that existing thermal insulation materials cannot achieve simultaneous improvement of mechanical properties and thermal insulation performance. At the same time, the composite film introduces a shell-like layered structure in the structural design, achieving a double improvement in strength and toughness.

[0019] 3. The template method for synthesizing micro-nano structural units in the present invention is universal and can be used for other metal oxides; in addition, the assembly strategy of the present invention is simple and can be expanded for production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a cross-sectional scanning electron microscope photograph of a 10 μm thick graphene oxide@zirconium oxide-sodium carboxymethyl cellulose composite film obtained in Example 1 of the present invention.

[0021] Figure 2 This is a stress-strain curve of the 10 μm thick graphene oxide@zirconium oxide-sodium carboxymethyl cellulose composite film obtained in Example 1 of the present invention.

[0022] Figure 3 This is the force and penetration depth curve of the 10 μm thick graphene oxide@zirconium oxide-sodium carboxymethyl cellulose composite film obtained in Example 1 of the present invention.

[0023] Figure 4 This is a cross-sectional scanning electron microscope photograph of a 20 μm thick graphene oxide@zirconium oxide-sodium carboxymethyl cellulose composite film obtained in Example 2 of the present invention.

[0024] Figure 5 This is a stress-strain curve of the 20 μm thick graphene oxide@zirconium oxide-sodium carboxymethyl cellulose composite film obtained in Example 1 of the present invention.

[0025] Figure 6 This is the force and penetration depth curve of the 20 μm thick graphene oxide@zirconium oxide-sodium carboxymethyl cellulose composite film obtained in Example 2 of the present invention.

[0026] Figure 7 This is a cross-sectional scanning electron microscope photograph of a 30 μm thick graphene oxide@zirconium oxide-sodium carboxymethyl cellulose composite film obtained in Example 1 of the present invention.

[0027] Figure 8 This is a stress-strain curve of the 30 μm thick graphene oxide@zirconium oxide-sodium carboxymethyl cellulose composite film obtained in Example 1 of the present invention.

[0028] Fig. 9 This is the force and penetration depth curve of the 30 μm thick graphene oxide@zirconium oxide-sodium carboxymethyl cellulose composite film obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The following is a detailed description of the preparation method of a lightweight, high-strength zirconium oxide-based thermal insulation film in conjunction with the accompanying drawings and examples. However, it should be understood that these examples are only used to illustrate the present invention and do not limit the scope of protection of the present invention in any way.

[0030] Example 1

[0031] Preparation method of 10 μm thick graphene oxide@zirconium oxide-sodium carboxymethyl cellulose composite film

[0032] The first step is to add hydrochloric acid and trihydroxyaminomethane to a round-bottom flask filled with 100-400mL deionized water to prepare a buffer solution with a pH of 7.6. After the pH stabilizes, add 40mg of graphene oxide nanosheets, stir evenly to obtain a brown-yellow suspension, then add 0.05g of zirconium oxychloride octahydrate, heat to 40°C in a water bath and react for 2.5 hours. After the reaction is completed, the product is centrifuged at 6000r / min for 5min, washed with deionized water 3-5 times, and the precipitate is evenly dispersed with deionized water to obtain a graphene oxide @ zirconium oxide nanosheet structural unit, and the volume is fixed for subsequent use;

[0033] The second step is to prepare an organic binder solution by adding 2.0 g of sodium carboxymethyl cellulose into a beaker containing 40 mL of deionized water to dissolve it;

[0034] In the third step, 30 mg of graphene oxide @ zirconium oxide nanosheet structural unit, 3 mL of organic binder solution, and 30 mL of deionized water were added to a small beaker in sequence, and stirred at room temperature for 18 hours. Then, the film was extracted using vacuum filtration assembly technology, and the obtained composite film was placed in a 50°C oven for drying. Finally, a 10 μm thick composite film was obtained. The cross-sectional SEM image of the composite film is shown in the figure below. Figure 1As shown in the figure, the nanosheets inside the film are stacked into a layered structure that mimics shells, and there are large and small pores between the layers. These pores restrict the flow of air, reduce the thermal conductivity, and thus improve the thermal insulation performance. The composite film was subjected to a tensile test, and the stress-strain curve obtained was shown in Figure 2 As shown, the tensile strength of the film is 175.7MPa and the toughness is 2.26MJ / m 3 The composite film was subjected to static compression by nanoindentation, and the force-indentation depth curve was obtained as shown in Figure 3 As shown, the Young's modulus is 4.8 GPa, the hardness is 0.3 GPa. The thermal conductivity of the composite film is measured to be 40 mW / (m·K).

[0035] Example 2

[0036] Preparation method of 20 μm thick graphene oxide@zirconium oxide-sodium carboxymethyl cellulose composite film

[0037] The first step is to add hydrochloric acid and trihydroxyaminomethane to a round-bottom flask filled with 100-400mL deionized water to prepare a buffer solution with a pH of 7.6. After the pH stabilizes, add 40mg of graphene oxide nanosheets, stir evenly to obtain a brown-yellow suspension, then add 0.10g of zirconium oxychloride octahydrate, heat to 40°C in a water bath and react for 2.5 hours. After the reaction is completed, the product is centrifuged at 6000r / min for 5min, washed with deionized water 3-5 times, and the precipitate is evenly dispersed with deionized water to obtain a graphene oxide @ zirconium oxide nanosheet structural unit, and the volume is fixed for subsequent use;

[0038] The second step is to prepare an organic binder solution by adding 2.0 g of polyvinyl alcohol into a beaker containing 40 mL of deionized water to dissolve it;

[0039] In the third step, 30 mg of graphene oxide @ zirconium oxide nanosheet structural unit, 3 mL of organic binder solution, and 30 mL of deionized water were added to a small beaker in sequence, and stirred at room temperature for 18 hours. Then, the film was extracted using vacuum filtration assembly technology, and the obtained composite film was placed in a 50°C oven for drying. Finally, a 20 μm thick composite film was obtained. The cross-sectional scanning electron microscope image of the composite film is shown in the figure. Figure 4 As shown in Figure 2, the internal layer structure of the film is more compact and the pores between the layers are smaller. The composite film is subjected to a tensile test and the stress-strain curve obtained is shown in Figure 2. Figure 5 As shown, the tensile strength of the film is 135.2MPa and the toughness is 2.12MJ / m 3 The composite film was subjected to static compression by nanoindentation, and the force-indentation depth curve was obtained as shown in Figure 6 As shown, the Young's modulus is 13.6 GPa, the hardness is 2.4 GPa. The thermal conductivity of the composite film is measured to be 45 mW / (m·K).

[0040] Example 3

[0041] Preparation method of 30 μm thick graphene oxide@zirconium oxide-sodium carboxymethyl cellulose composite film

[0042] The first step is to add hydrochloric acid and trihydroxyaminomethane to a round-bottom flask filled with 100-400mL deionized water to prepare a buffer solution with a pH of 7.6. After the pH stabilizes, add 40mg of graphene oxide nanosheets, stir evenly to obtain a brown-yellow suspension, then add 0.15g of zirconium oxychloride octahydrate, heat to 40°C in a water bath and react for 2.5 hours. After the reaction is completed, the product is centrifuged at 6000r / min for 5min, washed with deionized water 3-5 times, and the precipitate is evenly dispersed with deionized water to obtain graphene oxide @ zirconium oxide nanosheet structural units, and the volume is fixed for subsequent use;

[0043] The second step is to prepare an organic binder solution by adding 2.0 g of polyvinyl alcohol into a beaker containing 40 mL of deionized water to dissolve it;

[0044] In the third step, 30 mg of graphene oxide @ zirconium oxide nanosheet structural unit, 3 mL of organic binder solution, and 30 mL of deionized water were added to a small beaker in sequence, and stirred at room temperature for 18 hours. Then, the film was extracted using vacuum filtration assembly technology, and the obtained composite film was placed in a 50°C oven for drying. Finally, a 30 μm thick composite film was obtained. The cross-sectional SEM image of the composite film is shown in the figure below. Figure 7 As shown in Figure 2, the nanosheets are tightly packed and the formed layer is flatter. The composite film is subjected to a tensile test and the stress-strain curve obtained is shown in Figure 2. Figure 8 As shown, the tensile strength of the film is 85.85MPa and the toughness is 0.64MJ / m 3 The composite film was subjected to static compression by nanoindentation, and the force-indentation depth curve was obtained as shown in Fig. 9 As shown, the Young's modulus is 30.8 GPa, the hardness is 3.4 GPa. The thermal conductivity of the composite film is measured to be 51 mW / (m·K).

Claims

1. A method for preparing a lightweight and high-strength zirconium oxide-based thermal insulation film, characterized in that The following steps are involved: The first step is to add a buffer solution with a pH of 7-9 to a round-bottom flask filled with 100-400 mL of deionized water, add 10-40 mg of graphene oxide nanosheets after the pH stabilizes, stir evenly to obtain a brown-yellow suspension, then add 0.01-0.30 g of zirconium salt, heat in a water bath to 40-90 ° C and react for 1-3 hours. After the reaction is completed, the product is centrifuged and washed, and the precipitate is evenly dispersed with deionized water to obtain a graphene oxide @ zirconium oxide nanosheet structural unit, and the volume is fixed for subsequent use; The second step is to prepare an organic binder solution by adding 1.0-6.0 g of organic matter into a beaker containing 40 mL of deionized water to dissolve it; The third step is to add 5-50 mg of graphene oxide @ zirconium oxide nanosheet structural units, 1-5 mL of organic binder solution, and 30 mL of deionized water into a small beaker in sequence, stir at room temperature for 5-20 hours, then use vacuum filtration assembly technology to extract the film, and place the obtained composite film in a 50°C oven for drying.

2. The method for preparing a lightweight and high-strength zirconium oxide-based thermal insulation film according to claim 1, characterized in that: The buffer pair in the first step can be selected from an inorganic buffer pair and an organic buffer pair, preferably a hydrochloric acid-tris(hydroxymethyl)aminomethane buffer pair, and the buffer solution pH is preferably 7.6; the zirconium salt can be selected from zirconium nitrate, zirconium sulfate, zirconium oxychloride octahydrate, etc., and zirconium oxychloride octahydrate is preferred.

3. The method for preparing a lightweight and high-strength zirconium oxide-based thermal insulation film according to claim 1, characterized in that: The organic matter in the second step needs to form a good bonding effect with the graphene oxide@zirconia nanosheet structural unit, and can be selected from polyvinyl alcohol, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, etc., preferably sodium carboxymethyl cellulose.

4. The method for preparing a lightweight and high-strength zirconium oxide-based thermal insulation film according to claim 1, characterized in that: The composite film obtained by vacuum filtration in the third step is black, and the inside of the film has a layered structure imitating shells. There are pores between the layers, which is conducive to limiting air convection and thus reducing thermal conductivity.

5. The method for preparing a lightweight and high-strength zirconium oxide-based thermal insulation film according to claim 1, characterized in that: The obtained composite film has a light weight (density of 20-60 mg / cm 3 ), high strength (tensile strength is 60-200MPa), high toughness (toughness is 0.10-3.00MJ / m 3 ), outstanding thermal insulation performance (thermal conductivity is 30-70mW / (m·K)) and other advantages.

Citation Information

Patent Citations

  • Preparation method of bionic high-strength high-flexibility nano composite fiber

    CN110396731A

  • Preparation method of reduced graphene oxide / nano-zirconia composite material modified PI wear-resistant film

    CN113444391A

  • Preparation method of high-strength and high-toughness shell-imitated transparent composite material

    CN117164352A

  • Insulation type high-thermal-conductivity film and preparation method thereof

    CN117865688A

  • Method for uniformly growing intercalation medium in graphene oxide layered film

    CN118416705A

Cited By

  • Preparation method of zirconium oxide-based composite material with shell-like amorphous-crystal dual-phase structure

    CN119330704A